Mediating Role of e-Trust on the Relationship between Visual Social Media Marketing and Purchase Intention in Jordan - Hasan, Mohammad A.; Anuar, Marhana Mohamed; Al-Gasawneh, Jassim Ahmad; Yaakop, Azizul Yadi (International Review of Management and Marketing, 2025)
Jordanian real estate companies are currently dealing with difficult marketing conditions as the environment is becoming more competitive. The effect of visual social media marketing (VSMM) on customer purchase intention involving Jordanian real estate companies, was examined in this study, considering the mediating role of e-Trust. The Elaboration Likelihood Model (ELM) and Trust Model guided the development of the research framework. The research used quantitative survey techniques. A purposive sampling strategy was used in sample selection and online questionnaires were distributed via Google Forms on social media platforms. The link to the questionnaire was shared in social media groups related to Jordan’s real estate sector, resulting in 250 valid responses. To analyse the data and assess the hypotheses, partial least squares structural equation modelling (PLS- SEM) was used. The findings provide empirical evidence of the influence of VSMM and e-Trust on purchase intention. Additionally, the relationship between VSMM and purchase intention was mediated by e-Trust. This study theoretically fills gaps in the literature by integrating ELM and the Trust Model. Practically, the results of this study assist real estate companies in developing strategies to enhance purchases among potential customers. The results suggested that managers in the real estate companies need to focus on building e-Trust and VSMM.